State of Quality Engineering Practices: The Pakistan Perspective - Khan, M. N. A.; Mirza, A. M.; Shahid, M.; Wagan, R. A.; Saleem, I. (Engineering, Technology & Applied Science Research, 2020)
This study analyzes the state of quality engineering practices being exercised in the software industry of Pakistan. Statistics have been collected and analyzed to access important aspects of quality engineering including quality policy, review mechanism, quality assurance activities and practices, quality standards and models, and quality management systems. For this purpose, an elaborated questionnaire was prepared to pertain to various aspects of quality management and more than 30 software houses and software development organizations were surveyed in Islamabad and Rawalpindi. The survey results and a description of the concluding remarks are reported in this paper.